Going Offshore: Horseplay, Normalization and Sexual Harassment - Diffee, Chris (Columbia Journal of Gender and Law, 2013)
On November 7 or 8, Oncale was present when a new galleyhand complained to the Chevron company representative in charge of the Chevron platform about Pippen kissing that galleyhand and Lyons telling that galleyhand that Lyons “loved him” and wanted to “fuck him in his butt.” During a safety meeting the next morning, the Chevron company representative told Lyons and Pippen “not to mess with the galleyhand anymore,” explaining that the galleyhand was “new” and ““green to the field” and that the galleyhand “didn’t know how it was offshore.” Brief for Respondents, Oncale v. Sundowner Offshore Srvs., Inc., 523 U.S. 75 (1998) (No. 96-568), 1997 WL 634147, at *3.